Post COVID 19 Myocarditis: Clinical Case Series - ZOUZOU, Hanane (Clinical Medicine And Health Research Journal, 2024)
Corona virus disease 2019 infection exhibits a tropism for the respiratory tract, however several cardiac damages have been reported, such as coronary disease, cardiac arrhythmias and myocarditis; this latter has become more frequent after the outbreak of the COVID-19 pandemic, and may be the only manifestation of COVID 19 infection, the diagnosis is not always obvious especially for focal myocarditis and can be misdiagnosed as an acute coronary syndrome in some patients. We reported five patients, admitted between June 2020 and January 2021, in our cardiology department for isolated acute focal myocarditis secondary to COVID 19 infection without respiratory or other damages, the diagnosis was not evident at first, but further investigations such as: electrocardiographic evolution, magnetic resonance imagery, coronary computed tomography angiography, and COVID 19 antibody testing, were in favor of the diagnosis of focal myocarditis secondary to COVID 19 infection. Cardiac magnetic resonance imaging showed, delayed contrast enhancement in the lateral wall of the left ventricle, for all five patients, so fibrosis is preferentially located in the lateral wall, and the outcome was favorable without hemodynamic or arrhythmic complications.